1985
DOI: 10.1159/000158613
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Vessel Wall Morphology of Cerebral Cortical Arterioles after Short-Term Diabetes in Adult Rats

Abstract: Abstract. Microvascular pathology is one of the major problems associated with prolonged diabetes mellitus. The purpose of the present study was to determine if anatomical cellular pathology of the cerebral cortical microvessels could be detected very early after the onset of a streptozotocin-induced model of diabetes. Male rats at age 14-16 weeks were hyperglycemic (> 250 mg/dl) for 4 weeks prior to scanning and transmission electron microscopic analysis of the external and internal cell and vessel wall morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 8 publications
5
27
1
Order By: Relevance
“…Therefore, force transmission by the muscle to the circumference of the vessel should be equally efficient in normotensive and hypertensive rats, assuming there is little or no slippage of the VSM cells relative to the vessel wall in either strain of rats. Walmsley et al , x Miller, 18 Miller and colleagues, 17 ' " and Moore et al 23 have recorded a similar arrangement for VSM 29 have shown that active muscle tone did not substantially alter the orientation of the VSM cells relative to the vessel wall. We would expect similar circumstances for vessels of hypertensive rats because their VSM cells have a normal length and wrapping arrangement (see Table 1 and Figure 1, respectively).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, force transmission by the muscle to the circumference of the vessel should be equally efficient in normotensive and hypertensive rats, assuming there is little or no slippage of the VSM cells relative to the vessel wall in either strain of rats. Walmsley et al , x Miller, 18 Miller and colleagues, 17 ' " and Moore et al 23 have recorded a similar arrangement for VSM 29 have shown that active muscle tone did not substantially alter the orientation of the VSM cells relative to the vessel wall. We would expect similar circumstances for vessels of hypertensive rats because their VSM cells have a normal length and wrapping arrangement (see Table 1 and Figure 1, respectively).…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, reduced microsphere entrapment by SDI treatment in diabetic rats indicates a vascular effect, albeit not directly related to nutritive blood flow. Platelet aggregation, thrombus formation and leucocyte-endothelium interactions are increased in diabetes [71,72]. It is possible that SDI treatment might decrease one or more of these factors, which could explain reduced microsphere trapping and suggests a direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…1 In diabetic humans as well as experimental animals, morphological abnormalities, including arterial endothelial cell necrosis and thickened capillary basement membranes, have been observed in small cerebral vessels. [7][8][9] Besides these morphological changes, diabetic patients have also shown impaired cerebrovascular reactivity to hypercapnia, 10,11 acetazolamide, 12 and blood pressure changes. 13,14 These vascular changes may alter cerebral blood flow (CBF) and eventually produce a stroke.…”
mentioning
confidence: 99%